Childhood deaths from sexual abuse in Istanbul, Turkey: Medicolegal assessment - (:unkn) unknown (My University, 2006)
Aims: The evaluation of sexually abused children is a part of forensic medicine practice. Such assaults may result in the death of the victim due to different causes. Aim of this study was to present the childhood deaths determined as associated with sexual abuse according to smear results, genital and postmortem examinations, to determine the groups under the risk, and to contribute to the identification of the offenders. Methods: 17 cases of sexual child abuse with lethal outcome in the State Institute of Forensic Medicine in Istanbul, Turkey have been investigated in a five years' period from 1996 to 2000. Results: Most of the victims were female. In terms of cause of death, five cases were evaluated as general body trauma, three as gun shot, three as hanging, four as fatal pressure on the neck, one as strangulation with tie, one as narcotic intoxication. Conclusion: Such cases are very rare so that epidemiological conclusions concerning escalating violence of the youth cannot be drawn. However, sexual abuse of child resulting in death is the most severe form of an attack against the physical and psychological integrity of a still growing individual and its prevention requires a multidisciplinary approach, vigilance and the community's enhanced sensitivity to this topic. Death associated with sexual abuse is also dealt in this study. © Universitätsverlag Ulm GmbH 2006.
Keywords: Child; Death; Sexual abuse